PERSEPSI PETANI PADI SAWAH PADA CARA TANAM JAJAR LEGOWO DI KABUPATEN MAJALENGKA PROVINSI JAWA BARAT - Abdul Rojak -; Achdiyat - -; Soesilo Wibowo - (Jurnal Penyuluhan Pertanian, 2019)
ABSTRACTThe method of cultivating rice as one of the breakthroughs in increasing the productivity of paddy rice is the legowo row planting method. Sindangwangi Subdistrict, Majalengka District, most of the rice fields in one year farmers can do three times planting, this is because the water source is still stable. Jajar Legowo has been known by members of farmer groups and actively participates in activities. Based on the Agricultural Extension Program and the Annual Extension Work Plan for Sindangwangi District in 2018, the level of application of the legowo planting method has only reached 21% (118 of 559 people). This is inseparable from farmers' perceptions of the technology of planting jajar legowo included in the category of good enough (score 54.74). Respondents were 32 people aged 34 - 54 years and 14 people aged over 55 years, for elementary school education 36 people, junior high school 12 people, and SLA 2 people, while the duration of the study was 72% (36 people) over 10 years. Land area between 0.13 - 1 Ha is owned by 39 people, the level of knowledge of farmers is 27.82 (medium category) in the legowo row planting method. Factors that have a relationship with farmers' perception are the land area correlation coefficient 0.314 * and the level of knowledge of farmers correlation coefficient 0.870 **, indicating a strong and very strong level of relationship. ABSTRAKCara budidaya padi sebagai salah satu terobosan dalam peningkatan produktivitas padi sawah adalah cara tanam jajar legowo. Petani di Kecamatan Sindangwangi di Kabupaten Majalengka sebagian besar lahan sawahnya dalam satu tahun dapat melakukan tiga kali tanam, hal ini karena sumber air masih stabil. Tanam jajar legowo telah dikenal oleh anggota kelompoktani dan aktif mengikuti kegiatan. Berdasarkan Programa Penyuluhan Pertanian dan Rencana Kerja Tahunan Penyuluh Kecamatan Sindangwangi Tahun 2018, tingkat penerapan cara tanam jajar legowo baru mencapai 21% (Sampel petani 118 dari 559 orang). Hal ini tidak terlepas dari persepsi petani terhadap teknologi cara tanam jajar legowo termasuk dalam kategori cukup baik (skor 54,74). Responden sebanyak 32 orang berumur 34 – 54 tahun dan 14 orang berumur di atas 55 tahun, untuk pendidikan tamat SD 36 orang, SLTP 12 orang, dan SLA 2 orang, sedangkan lama berusahatani sebanyak 72% (36 orang) di atas 10 tahun. Luas lahan antara 0,13 – 1 Ha dimiliki oleh 39 orang, tingkat pengetahuan petani skor 27,82 (kategori sedang) dalam cara tanam jajar legowo. Faktor – faktor yang memiliki hubungan dengan persepsi petani adalah luas lahan koefisien korelasi 0,314* dan tingkat pengetahuan petani koefisien korelasi 0,870**, menunjukkan tingkat hubungan yang kuat dan sangat kuat.